How to Effectively Boost Fat Oxidation by Calorie Restriction in Overweight and Obese Adults? - Rima Solianik; Artūras Sujeta; Kristina Justinavičienė; Laura Žlibinaitė (Lithuanian Sports University, 2019)
Background. It is clinically important to determine the factors that increase fat oxidation and have potential to improve body composition in overweight and obese individuals. Thus, the aim of the present study was to compare the effects of a 2-day very low-calorie diet and 2-day zero-calorie diet on fat oxidation and prospective food consumption in overweight and mildly obese adults. Methods. Eighteen subjects (body mass index above 25 kg/m2) aged 19-33 years were tested under two conditions allocated randomly: 2-day zero-calorie diet with water provided ad libitum and 2-day very-low calorie diet. Appetite sensations, mood state, inhibitory control, and substrate oxidation were evaluated before and after each diet. Results. Greater increase in fat oxidation (p < .05) was observed after zero-calorie diet when compared to a very low-calorie diet. Results showed that both diets increased (p < .05) sensation of hunger and prospective food consumption, whereas no changes were observed in inhibitory control. Greater decrement for vigor (p < .05) was observed after zero-calorie diet when compared to a very low-calorie diet, whereas other mood states were not affected by it. Conclusion. Intermittent fasting with zero-calorie diet may boost fat oxidation to a greater extent when compared to very low-calorie diet and may assist with weight loss in overweight and mildly obese adults.